Responsible research and innovation: A conceptual contribution to theory and practice of technology management - Lukasz Nazarko (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
The concept of Responsible Research and Innovation (RRI) has become a popular term as a result of making it a cross-cutting theme for the Horizon 2020 Framework Programme of the European Union. RRI may be understood as a process by which societal actors and innovators become mutually responsive to each other with a view to the acceptability, sustainability and societal desirability of the innovation process and its products. The work presents a review of the state-of-art scientific literature on Responsible Research and Innovation (RRI) together with a synthesis of theoretical and practical challenges faced by this new concept. Mapping of RRI dimensions and its theoretical assumptions is performed. Bibliometric analysis of the scientific literature on RRI is carried out. The analysis of RRI-related projects is conducted. The attempt is made to clarify what RRI means for an enterprise in practical terms and what makes an innovation project in an enterprise a responsible one. Finally, a proposal for a closer interchange between RRI and Technology Assessment discourses is made together with an argument for a more extensive use of future-oriented methods that increase epistemic horizons of an innovating organisation.
Keywords: O32; O33; O38; 650; Responsible Research and Innovation (RRI); responsibility; European Union; innovation; technology management; technology assessment